GROUNDS FOR APPLYING TO THE COURT WITH A CLAIM FOR COLLECTION OF ALIMENTS - A SENSELESS GAP - Расторгуєв, Олександр Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to determine and outline the grounds for going to court with a claim for alimony. Research methods: the methodological basis of the research was general scientific methods of cognition, by which the author tried to find out the criteria for determining the grounds for going to court with a claim for alimony. Results: the author identifies and sees the need to specify and regulate the grounds for going to court with a claim for alimony. Discussion: the author proposes to consider the scope of the obligation of parents to maintain their children until they reach the age of majority in order to further fully understand the violation of such a duty as grounds for filing a lawsuit for alimony. Alimony, as a material expression or form of parental responsibility for the maintenance of children until they reach the age of majority, ensures that the child’s rights to material security are properly respected. There are no questions to the theoretical side of these concepts. However, in practice there are serious problems, the history of which probably has very deep roots. Understanding the grounds for going to court with a claim for alimony, the person who has the right to file such a claim, as well as the procedure for considering such applications in the context of the normative consolidation and traditionalism as such, raises serious concerns. First of all, the formalism of the courts in this category of cases leads to a gross violation of the rights of defendants to protect their rights, as well as the fundamental principles of civil justice - equality before the law, adversarial, proportional and dispositive.The thesis on the possibility of determining the grounds for going to court with a claim for recovery of alimony on a practical example is discussed.